Influence of hexanol/hydrogen additives with diesel fuel from CRDI diesel engine with exhaust gas recirculation technique: A special focus on performance, combustion, gaseous and emission species. (15th March 2022) - Seelam, Navyasree; Gugulothu, Santhosh Kumar; Reddy, Ragireddy Venkat; Burra, Bhasker
Abstract: Emission and combustion parameters of common rail direct injection combustion engine with different proportions of exhaust gas recirculation rate and 1-hexanol blends with hydrogen on performance are the main motive of this research. To lessen the dependency on diesel fuel and reduce harmful emissions, 1-hexanol is used, as it has better fuel properties than small-carbon-chain alcohol, and it can be blended with diesel. In common rail direct injection combustion engine, a research was conducted, in which fuel blends (1-hexanol-diesel) were variant, i.e., (10%, 20%, 30%) by volume whereas engine speed was fixed at 1500 rpm by varying the load at 25% step from 25 to 100%. Blends were examined with various exhaust gas recirculation rates (10% and 20%) to see what impact they have on engine properties. It was observed that the higher the proportion of 1-Hexanol, the lower the engine performance. The research revealed that for the blend D70H30/H2, around 8.24% rise in brake specific fuel consumption, slight rise in hydrocarbon, 2.80% reduction in brake thermal efficiency, and 16.70% reduction in nitrogen oxides (NOx ) emission. With 1-hexanol-diesel-hydrogen blends, the engine is noted to function effortlessly, so as a substitute to the diesel up to 30% of the 1-hexanol can be used while increasing the total cost of implementation. Highlights: Effect of oxygen additives on CRDI diesel engine. Diesel/1-hexanol blends reduce the MGT and CP. BTE is observed to reduce for hexanol/hydrogen blended with diesel. Emissions like HC, CO, NOx and smoke are reduced with oxygen additives.